Sintesis dan Karakterisasi Nanokomposit ZnO/NiFe2O4 dari Limbah Baterai menggunakan Metode Solid State sebagai Fotokatalis Zat Warna Metilen Biru - FAHMI SHIHAB; EKO PRABOWO HADISANTOSO; SONI SETIADJI (Gunung Djati Conference Series, 2022)
Methylene blue is included in B3 Waste which is toxic, mutagenic and carcinogenic. In the form of liquid waste, this substance is a source of water pollution. To overcome this pollution, an efficient alternative method is photocatalysis. Compounds that have the potential as photocatalysts and are in great demand lately are ZnO semiconductor compounds. Its nature as a photocatalyst is able to reduce the intensity of dye waste in the aquatic environment. Behind its ability to reduce the intensity of dyestuffs, ZnO itself has a large band gap value and diamagnetic properties which make it one of the drawbacks. To improve the magnetic properties and reduce the value of the existing band gap, it is necessary to composit with magnetic compounds such as NiFe2O4. Therefore, ZnO and NiFe2O4 compounds can be synthesized into ZnO/NiFe2O4 nanocomposites which have higher potential as photocatalysts that work in visible light and UV light and their magnetic properties can facilitate the separation process. ZnO was synthesized by precipitation method while NiFe2O4 was synthesized by coprecipitation method, while ZnO/NiFe2O4 nanocomposite was synthesized from battery waste as a source of Zn and Fe. The solid state method was used in the synthesis of ZnO/NiFe2O4 with three mole variations of ZnO:NiFe2O4 in a ratio of 1:2, 1:1, and 2:1 which were calcined at a temperature of 800 . XRD characterization results showed a fierce phase on ZnO and tetravorite on NiFe2O4 with hexagonal and cubic crystal forms with crystal sizes ranging from 30-32 nm. The SEM results showed a uniformity of shape with a polydispersity value of less than 0.5 with a nanospheric morphology. ZnO/NiFe2O4 nanocomposite formed from battery waste was applied to reduce the intensity of methylene blue dye. The best conditions were found in ZnO/NiFe2O4 2:1 with a photocatalyst mass of 50 mg for 180 minutes with a concentration of 10 ppm methylene blue and a pH of 11.